Airway Clearance Techniques: The Right Choice for the Right Patient - Belli, Stefano; Prince, Ilaria; Savio, Gloria; Paracchini, Elena; Cattaneo, Davide; Bianchi, Manuela; Masocco, Francesca; Bellanti, Maria Teresa; Balbi, Bruno (Frontiers in Medicine, 2021)
The management of bronchial secretions is one of the main problems encountered in a wide spectrum of medical conditions ranging from respiratory disorders, neuromuscular disorders and patients undergoing either thoracic or abdominal surgery. The purpose of this review is illustrate to the reader the different ACTs currently available and the related evidence present in literature. Alongside methods with a strong background behind as postural drainage, manual techniques or PEP systems, the current orientation is increasingly aimed at devices that can mobilize and / or remove secretions. Cough Assist, Vacuum Techniques, systems that modulate airflow have more and more scientific evidence. Different principles combination is a new field of investigation that goes towards an increasing of clinical complexity that will facing us.